Do logging concessions decrease the availability to villagers of foods from timber trees? A quantitative analysis for Moabi (Baillonella toxisperma), Sapelli ( Entandrophragma cylindricum ) and Tali (Erythrophleum suaveolens) in Cameroon - Noutcheu, R.; Snook, Laura K.; Tchatat, M.; Taedoumg, H.E.; Tchingsabe, O.; Tieguhong, J.C. (Elsevier, 2016)
Many species of timber trees in Cameroon are exploited by logging companies for timber and by forest- dependent communities for non-timber forest products (NTFPs). Quantitative analyses were conducted within and near forest concessions in Cameroon to determine the density of multiple use tree species that provide both timber for industry and foods consumed by local populations (fruit and oil or edible caterpillars), and how this has been affected by logging. Individuals of the three species (Moabi, Baillonella toxisperma; Sapelli, Entandrophragma cylindricum; and Tali, Erythrophleum suaveolens ), including their stumps, were identified and measured on 5 ha (100 m 500 m) sample plots around 4 villages and in 2 concessions. Around each village 21 sample plots, stratified by distance, were laid out along three transects extending 10 km towards the concession, each oriented 45 from the other. In concessions, 20 plots were established within the 2012 cutting unit after timber harvesting, using a stratified random system. Moabi trees occurred at the lowest densities: around villages, 22.8 ± 3.3/100 ha of precommercial individuals and 5.0 ± 1.4/100 ha of individuals of harvestable size (P80 cm dbh); on concessions, 7.5 ± 2.4 precommercial trees/100 ha, and 0–2.0 ± 1.4/100 ha harvestable individuals. Densities of Sapelli trees were not significantly different between villages and concessions, averaging 32.6 ± 3.8/100 ha and 37.5 ± 5.5/100 ha, respectively, for precommercial sizes and 9.5 ± 2.2/100 ha and 6 ± 1.6/100 ha, respectively, for harvestable trees ( P 100 cm dbh). Pre-commercial Tali trees occurred at lower densities (3.8 ± 0.9/100 ha) around villages, as compared to 11.5 ± 3.1/100 ha on concessions. Harvestable Tali trees (P 60 cm dbh) occurred at the same densities around villages and on concessions (56.0 ± 7.2/100 ha). Half, or more, of commercial-sized trees of caterpillar-hosting species were left standing after harvest on concessions (89–94% of Tali; 50–79% of Sapelli), reflecting constraints due to timber quality, market demand and inaccessibility. No harvestable Moabi trees were logged from the 2012 cutting areas, reflecting agreements between communities and concessionaires to leave them for fruit and oil, but densities were so low it will be important that villagers conserve those around their villages. Stumps of all three species were found around villages, revealing that mechanisms for negotiation are also needed among villagers with interests in either timber or non-timber resources obtained from the same tree species.